STATISTICAL SIMULATION OF WOOD DENSITY CHANGES DUE TO THERMAL TREATMENT IN CARBON DIOXIDE ATMOSPHERE - Maksymiv, Volodymyr; Andrashek, Yosyp; Shchupakivskyy, Roman; Bilyk, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2012)
The aim of the present investigation was to detect changes, and make statistical simulation, of oak (Quercus robur) density, due to the influence of thermal modification parameters. The reduction of the density was recorded by High-Frequency Densitometry. To achieve a comparison of the initial density and the resulting density of thermal treatment, the examination was carried out on the same sample. As a result, an adequate regression model ∆ρ0 = f(T, ν, τ) was obtained for dry wood density changes ∆ρ0 of oak with respect to temperature T, heating rate ν, and hold-up time at treatment temperature τ. The obtained results made it possible to present visually plots of nonlinear influence of modification parameters (T, ν, τ) on oak wood density changes during heat treatment in carbon dioxide atmosphere